2011
DOI: 10.3354/meps08974
|View full text |Cite
|
Sign up to set email alerts
|

Diatom to dinoflagellate shift in the summer phytoplankton community in a bay impacted by nuclear power plant thermal effluent

Abstract: Understanding how nuclear power plant thermal effluents influence the phytoplankton community may provide insights into the potential ecological consequences of global warming. In the present study, long-term trends in the phytoplankton community structure under the influence of nuclear power plant thermal effluent in the subtropical Daya Bay (DYB) in China were investigated in the summer season from 1982 to 2005. Water temperature at the outfall station was significantly higher than in the surrounding water, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 18 publications
(29 reference statements)
1
28
0
Order By: Relevance
“…Similarly, Li et al (2011) found that the contribution of diatoms and dinoflagellates to the total phytoplankton population showed significant correlation with temperature, negative for diatoms, while positive for dinoflagellates. In the present study the species composition showed 46 -100% and 58 -71% differences between the outlet and intake of NPP I and NPP II for each season, respectively (calculated by similarity indices, data not shown).…”
Section: Preliminary Observations On the Effect Of Thermal Dischargesmentioning
confidence: 98%
See 4 more Smart Citations
“…Similarly, Li et al (2011) found that the contribution of diatoms and dinoflagellates to the total phytoplankton population showed significant correlation with temperature, negative for diatoms, while positive for dinoflagellates. In the present study the species composition showed 46 -100% and 58 -71% differences between the outlet and intake of NPP I and NPP II for each season, respectively (calculated by similarity indices, data not shown).…”
Section: Preliminary Observations On the Effect Of Thermal Dischargesmentioning
confidence: 98%
“…It was reported that in the outlet area of power plants the seawater temperature increased about 8 -12°C in temperate zones (Bamber 1995) and 6 -10°C in tropical areas (Martínez-Arroyo et al 2000;Poornima et al 2006). In the subtropical Daya Bay in China, Li et al (2011) also suggested that the seawater temperature at the outfall station was significantly higher than in the surrounding water, by as much as 5.6°C, and increased by 6.8°C during the 23-year study period. Although we did not have sufficient temperature data on the NPP outlet, temperature records for NPP II outlet and intake during 2001 -2003 were available from two previous studies.…”
Section: Preliminary Observations On the Effect Of Thermal Dischargesmentioning
confidence: 98%
See 3 more Smart Citations